Scabies in Koranic schools in Dakar, Senegal: Comparison of two therapeutic modalities - Fatimata, Ly; Adama, Faye; Issa, Wone; Souleye, Lelo; Astou, Diouf; Abou, Koundio; Tene, Ndiaye Diop Mame; Fatou, Gueye Diagne; Aminata, Deh; Babacar, Faye; Oumar, Toure Fall Awa; Antoine, Mahé; Anta, Tall Dia (YCAB Publisher & IAKMI SULTRA, 2021)
Background: In 2017, WHO recognized scabies as a neglected tropical disease. The optimal treatment is not well defined in some communities.Objective: This study aimed to compare ivermectin and benzyl benzoate in the treatment of scabies in Koranic schools (or